Effect of interval training program on rate-pressure product in the management of hypertension in black African male subjects - Lamina, Sikiru; Okoye, Goddy; Ezema, Charles; Anele, Theresa; Ezugwu, Anthonia (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Rate-pressure product is a determinant of cardiovascular risk in patient with hypertension and one of the major predictors of myocardial oxygen consumption.Aim: The primary purpose of the present study was to investigate the effect of interval training program on rate-pressure product in subjects with hypertension.Materials and Methods: Two hundred and forty-five male patients of essential hypertension with mild to moderate systolic blood pressure between 140 and 179 mmHg and diastolic blood pressure between 90 and 109 mmHg were age-matched and grouped into interval group (n= 140) and control group (n= 105). The interval (work:rest ratio of 1:1) group was involved in an 8-week interval training program of between 45 and 60 min at intensities of 60-79% of the maximum heart rate, while the control group remained sedentary during this period. Blood pressure, maximum volume of oxygen consumed (VO2max), and rate-pressure product were assessed.Results: Findings of the study revealed significant effect of exercise training program on rate-pressure product and VO2max. The correlation of rate-pressure product with systolic blood pressure was much stronger (87% variance) atP< 0.05.Conclusion: It was concluded that moderate intensity interval training program is an effective means of lowering myocardial oxygen consumption and an adjunct non-pharmacological management of essential hypertension.
Keywords: Hypertension; interval exercise; rate-pressure product